PENGARUH KETERLIBATAN KERJA, SIKAP KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PERTANIAN KABUPATEN MANDAILING NATAL - Juli Hidayah; Ali Toris; Armin Syahputra Hakim Harahap; Meirawaty Nasution; Rahma Dewi (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
This research aims to determine and analyze the influence of work involvement, work attitude and organizational commitment on the performance employees of Dinas Pertanian Kabupaten Mandailing Natal, both partially and simultaneously. The sample in this research amounted to 63 people taken using the stratified random sampling method. The results showed : 1) work involvement had a positive and significant effect on the performance employees of Dinas Pertanian Kabupaten Mandailing Natal; 2) work attitude has a positive and significant effect on the performance employees of Dinas Pertanian Kabupaten Mandailing Natal; 3) organizational commitment has a positive and significant effect on the performance employees of Dinas Pertanian Kabupaten Mandailing Natal; 4) work involvement, work attitude and organizational commitment have a positive and significant effect on the performance employees of Dinas Pertanian Kabupaten Mandailing Natal. The performance employees is able to be influenced by work involvement, work attitude and organizational which amounted to 53.9%, while the remaining 46.1% was influenced by other variables not examined in this research.